2014
DOI: 10.1038/hdy.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Divergent selection for opsin gene variation in guppy (Poecilia reticulata) populations of Trinidad and Tobago

Abstract: The guppy is known to exhibit remarkable interindividual variations in spectral sensitivity of middle to long wavelength-sensitive (M/LWS) cone photoreceptor cells. The guppy has four M/LWS-type opsin genes (LWS-1, LWS-2, LWS-3 and LWS-4) that are considered to be responsible for this sensory variation. However, the allelic variation of the opsin genes, particularly in terms of their absorption spectrum, has not been explored in wild populations. Thus, we examined nucleotide variations in the four M/LWS opsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 62 publications
1
37
1
Order By: Relevance
“…Dissolved oxygen has been used as a proxy for differences in lighting environment elsewhere (Tezuka et al . ), yet for this environmental variable, we still found no differences between high‐ and low‐predation populations in either the Aripo ( t = −0.0354, P = 0.9736) or the Marianne ( t = −1.7165, P = 0.1954) watersheds. We also found no significant differences between high‐ and low‐predation populations within watershed for temperature (Aripo— t = −1.2522, P = 0.2817; Marianne— t = 0.3288, P = 0.7629), conductivity (Aripo— t = 4.0328, P = 0.0529; Marianne— t = 1.4242, P = 0.2332), pH (Aripo— t = −0.5048, P = 0.6593; Marianne— t = 1.8954, P = 0.1311) or total dissolved solids (Aripo— t = −0.3474, P = 0.7602; Marianne— t = 1.4661, P = 0.2218).…”
Section: Resultsmentioning
confidence: 59%
“…Dissolved oxygen has been used as a proxy for differences in lighting environment elsewhere (Tezuka et al . ), yet for this environmental variable, we still found no differences between high‐ and low‐predation populations in either the Aripo ( t = −0.0354, P = 0.9736) or the Marianne ( t = −1.7165, P = 0.1954) watersheds. We also found no significant differences between high‐ and low‐predation populations within watershed for temperature (Aripo— t = −1.2522, P = 0.2817; Marianne— t = 0.3288, P = 0.7629), conductivity (Aripo— t = 4.0328, P = 0.0529; Marianne— t = 1.4242, P = 0.2332), pH (Aripo— t = −0.5048, P = 0.6593; Marianne— t = 1.8954, P = 0.1311) or total dissolved solids (Aripo— t = −0.3474, P = 0.7602; Marianne— t = 1.4661, P = 0.2218).…”
Section: Resultsmentioning
confidence: 59%
“…This content downloaded from 130.092.009.056 on February 07, 2017 07:14:13 AM variation in visual environments and variation in fish visual properties (e.g., Carleton et al 2005;Fuller et al 2005;Davies et al 2009;Hofmann et al 2009) and signatures of selection on visual pigment genes (e.g., Terai et al 2006;Hofmann et al 2009Hofmann et al , 2012Larmuseau et al 2010;Weadick et al 2012;Tezuka et al 2014;Gaither et al 2015;TorresDowdall et al 2015). Some of the strongest evidence comes from populations of the Lake Victoria cichlids Pundamilia pundamilia and Pundamilia nyererei, in which the extent of depth segregation between these two species, causing exposure to different visual environments, correlates with the extent of divergence in visual properties, visual communication traits, and reproductive isolation .…”
Section: Fitness Effects Of Sensory Divergence 81mentioning
confidence: 99%
“…The light environment is a factor known to drive both the reception and production of visual signals of fishes (Hornsby et al 2013;Hurtado-Gonzales et al 2014;Shin and Choi 2014;Terai et al 2006;Tezuka et al 2014). Indeed, the present study showed that the spectral sensitivities of P. h. himantegus and P. h. chii are distinct: P. h. himantegus is more sensitive than P. h. chii to longer wavelength light, while it is less sensitive than P. h. chii at shorter wavelengths.…”
Section: Discussionmentioning
confidence: 58%
“…For example, the spectral sensitivity of milkfish (Chanos chanos), humpback salmon (Oncorhynchus gorbuscha), and yellowfin tuna (Thunnus albacares) ontogenetically change to fit the photic environment during each developmental stage (Chang et al 2009a;Cheng and Flamarique 2004;Loew et al 2002). Moreover, it has been reported that spectral sensitivity has evolved to adapt to environmental light parameters in cichlids, seabreams, and moray eels (Seehausen et al 2008;Wang et al 2011;Wang et al 2009), especially, the adaptations of RH1 and LWS opsins to light environments which are documented in cichlid fishes (Sugawara et al 2005;Terai et al 2006), as well as in different populations of three-spined stickleback (Gasterosteus aculeatus) and guppy (Poecilia reticulata) (McDonald and Hawryshyn 1995;Tezuka et al 2014). The retinal photoreceptor cells of fishes utilize visual pigments, which contain a chromophore (11-cis-retinal, A1 retinal, or 11-cis-3,4-dehydroretinal, A2 retinal) and opsin, to capture photons.…”
Section: Introductionmentioning
confidence: 99%